PENYUSUNAN KOMPONEN KURIKULUM SEBAGAI FONDASI PENINGKATAN MUTU PEMBELAJARAN DI LEMBAGA PENDIDIKAN ISLAM - Sulfadli Sulfadli; Sri Mulya Nengsi; Muslimin Muslimin; Suciatmi Suciatmi; Herda Herda (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2023)
This study aims to comprehensively analyze the structuring of curriculum components as a foundation for improving the quality of learning in Islamic educational institutions. The main objective of the study is to understand how curriculum components can be designed systematically and integratively to serve as a strong basis for sustainable improvement in learning quality within the context of Islamic education. The main aspects discussed in this study include: the definition of curriculum component structuring; the main components of the curriculum (educational objectives, learning content or materials, learning strategies or processes, and evaluation of learning outcomes); the role of supporting curriculum components (graduate profile, learning outcomes map, and Semester Learning Plan/RPS); principles of curriculum component structuring; curriculum design models (Tyler, Taba, and OBE); and challenges faced in curriculum development in Islamic educational institutions, including misalignment between Graduate Learning Outcomes (CPL) and learning content, weak integration of the Merdeka Belajar–Kampus Merdeka policy, gaps in graduate competencies, and limited lecturer capacity in curriculum design. This analysis aims to provide a deeper understanding of how curriculum components can be designed systematically and integratively to become a strong foundation for sustainable improvement in learning quality, as well as how curriculum design principles and models can be effectively implemented in the context of Islamic education. The study employs a library research approach with a qualitative-descriptive analysis method of relevant scientific sources, such as books, academic journals, previous research findings, curriculum-related regulations, and official documents related to Islamic education. Data were analyzed through a thematic categorization process to map the conceptual framework, principles, and challenges of curriculum component structuring in the context of Islamic education. The results show that the structuring of curriculum components must be based on Graduate Learning Outcomes (CPL) covering aspects of attitudes, knowledge, general skills, and specific skills, and must integrate religious and general sciences holistically. Coherent, relevant, flexible, and comprehensive curriculum components are key to creating active, contextual, and learner-centered learning. In addition, curriculum implementation requires careful planning, active involvement of educators, alignment with the Merdeka Belajar–Kampus Merdeka policy, and enhancement of lecturers’ capacity in curriculum design. The novelty of this study lies in the integration of modern curriculum design approaches (OBE) with the context of Islamic education, while also highlighting the strategic role of supporting curriculum components such as the graduate profile, learning outcomes map, and Semester Learning Plan (RPS). These findings provide important implications for administrators of Islamic educational institutions, curriculum developers, and educators in designing and implementing curricula that are relevant, coherent, and oriented toward the formation of competent, adaptive, and Islamic-minded graduates.